2018
DOI: 10.5194/acp-18-16601-2018
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and horizontal distribution of regional new particle formation events in Madrid

Abstract: Abstract. The vertical profile of new particle formation (NPF) events was studied by comparing the aerosol size number distributions measured aloft and at surface level in a suburban environment in Madrid, Spain, using airborne instruments. The horizontal distribution and regional impact of the NPF events was investigated with data from three urban, urban background, and suburban stations in the Madrid metropolitan area. Intensive regional NPF episodes followed by particle growth were simultaneously recorded a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 80 publications
4
25
0
1
Order By: Relevance
“…In the Madrid metropolitan area the main local source of primary UFP is traffic (Brines et al, 2015). In the summer period, UFP generated by nucleations can also appear at the regional scale (Carnerero et al, 2018). The nucleation precursor gases can be anthropogenic and biogenic.…”
Section: Air Pollutants Data From Air Quality Monitoring Stationsmentioning
confidence: 99%
“…In the Madrid metropolitan area the main local source of primary UFP is traffic (Brines et al, 2015). In the summer period, UFP generated by nucleations can also appear at the regional scale (Carnerero et al, 2018). The nucleation precursor gases can be anthropogenic and biogenic.…”
Section: Air Pollutants Data From Air Quality Monitoring Stationsmentioning
confidence: 99%
“…Due to the role of NPF in the production of CCN, it is of special interest to characterise NPF in the free troposphere (FT) and its vertical distribution. However, only a few studies have focused on the vertical distribution of these events (e.g., Carnerero et al, 2018;Komppula et al, 2003) and the existing observations of NPF at high altitudes provide contradictory results. For example, Crumeyrolle et al (2010) showed that the occurrence of NPF events was limited to the planetary boundary layer (PBL), while Hamburger et al (2011) have reported the presence of high concentrations of ultrafine particles in the upper FT, and Boulon et al (2011) found that the nucleation processes were more frequent in a high-altitude site than in the PBL, due to enhanced ion contribution to NPF at high altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Regional CTMs have been used to investigate O 3 pollution in Spain in several studies. Most of these studies aimed to describe short-term (rarely exceeding 5 d) pollution events (Toll and Baldasano, 2000;Jiménez et al, 2005Jiménez et al, , 2006San José et al, 2005;Carvalho et al, 2006;Valverde et al, 2016;Pay et al, 2018) and, in some cases, to discuss the effectiveness of potential mitigation strategies (Palacios et al, 2002;Soret et al, 2014). Despite these efforts, work is still needed to evaluate the impact of changes in the vertical configuration of CTMs, especially in the Mediterranean region where the atmospheric dynamics in summer is characterised by complex recirculation processes with effective vertical exchange (Millán et al, 1997(Millán et al, , 2000Gangoiti et al, 2001;Borge et al, 2010;Querol et al, 2017Querol et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In the Iberian Peninsula, the use of fine grids (in the order of 1-5 km× 1-5 km) has been found to be beneficial in the context of complex terrains where mesoscale processes acquire importance for interpreting production and transport of O 3 (Toll and Baldasano, 2000;Jiménez-Guerrero et al, 2008). In coastal areas, with complex topography, high-resolution simulations have been generally employed with good results (Carvalho et al, 2006;Jiménez et al, 2006;Gonçalves et al, 2009). Moreover fine grids have been recommended for describing O 3 variability especially in urban and industrial areas (Jiménez et al, 2006;Baldasano et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation